The Impact of University Level Sports Education on Social Media Addiction - Okudan, Bilal; Karakullukçu, Ömür Fatih (Asian Journal of Education and Training, 2021)
The aim of this study is to analyse the effects of university level sport education on social media addiction. For this purpose, social media addiction scales filled in by 320 students from the faculty of Sports Sciences and 333 students from the faculty of Education were evaluated. T-test, one-way variance analysis (ANOVA) and LSD test were used in statistical procedures. In the study, occupation, mood modification, relapse and conflict scores were found to be statistically significantly different in terms of gender (p<0.05 and p<0.001). Statistically significant difference was also found in social media addiction total score in terms of the year of study (p<0.05 and p<0.001). Occupation, mood modification, relapse, conflict and social media addiction scale scores of faculty of sport sciences students were found to be lower than the scores of education faculty students (p<0.001). Conclusion: It was found that social media addiction level of students receiving sport education was lower when compared with students who were not receiving sport education and it was concluded that sport education could be effective in decreasing social media addiction. It can be recommended to provide opportunities to receive sport education and to do sport to university students who are not receiving sport education.